2001
DOI: 10.1038/sj.cgt.7700290
|View full text |Cite
|
Sign up to set email alerts
|

Necrotic, rather than apoptotic, cell death caused by cytochrome P450–activated ifosfamide

Abstract: Feline kidney cells were transfected with a vector overexpressing cytochrome P450 2B1 ( CYP2B1 ) . Transfected cells acquired a new specific biochemical activity, which could be demonstrated by a rapid CYP2B1 detection assay and showed selective sensitivity to the antitumorigenic prodrug ifosfamide ( IFO ) . Further, the cell -killing effect was also mediated on nonmodified cells like feline kidney cells, mouse lymphoma, and human pancreatic cells in the vicinity of the CYP2B1 -expressing cells due to the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Caspase-3,-8 and -9 activation was also observed in Chinese hamster cells, which were hypersensitive to the cytostatic drug -d-glucose-ifosfamide mustard 37 . In contrast to these reports, Karle et al 38 demonstrated a necrotic rather than an apoptotic mechanism of an activated ifosfamide metabolite, phosphoramide mustard, on various tumour cells. However, the results regarding either the z-VAD-fmk experiments or else the caspase-3, -8 and -9 activities clearly demonstrate caspase-dependent apoptosis induced by 4OOH-IFA in human leukaemia cells.…”
Section: Discussionmentioning
confidence: 87%
“…Caspase-3,-8 and -9 activation was also observed in Chinese hamster cells, which were hypersensitive to the cytostatic drug -d-glucose-ifosfamide mustard 37 . In contrast to these reports, Karle et al 38 demonstrated a necrotic rather than an apoptotic mechanism of an activated ifosfamide metabolite, phosphoramide mustard, on various tumour cells. However, the results regarding either the z-VAD-fmk experiments or else the caspase-3, -8 and -9 activities clearly demonstrate caspase-dependent apoptosis induced by 4OOH-IFA in human leukaemia cells.…”
Section: Discussionmentioning
confidence: 87%
“…6, 7). CPA and IFA are alkylating agent prodrugs that induce DNA cross-linking in a cell cycle-independent manner, and ultimately trigger a mitochondrial pathway apoptotic cell death in the case of CPA (8) and either apoptosis or necrosis in the case of IFA (8,9). CPA and IFA are activated by a subset of liver-expressed P450 enzymes (10,11), which catalyze a 4-hydroxylation reaction that yields cell membrane-permeable, cytotoxic metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Feline kidney cells have been transfected with a vector that overexpresses cytochrome P450-2B1. 36 Transfected cells acquire biochemical activity and are able to activate prodrug ifosfamide, but the potential deleterious effects of inactive metabolites have not been examined. Mesna (sodium 2-mercaptoethanesulfonate) combines with acrolein in the urinary bladder and is effective in preventing urothelial toxicosis in humans treated with ifosfamide; however, it does not protect against ifosfamideinduced nephrotoxicosis.…”
Section: Discussionmentioning
confidence: 99%